A critical examination of empowerment discourse in medical tourism: the case of the dental tourism industry in Los Algodones, Mexico - Krystyna Adams; Jeremy Snyder; Valorie A. Crooks; Nicole S. Berry (BMC, 2018)
Abstract Background Medical tourism is a term used to describe the phenomenon of individuals intentionally traveling across national borders to privately purchase medical care. The medical tourism industry has been portrayed in the media as an "escape valve" providing alternative care options as a result of vast economic asymmetries between the global north and global south and the flexible regulatory environment in which care is provided to medical tourists. Discourse suggesting the medical tourism industry necessarily enhances access to medical care has been employed by industry stakeholders to promote continued expansion of the industry; however, it remains unknown how this discourse informs industry practices on the ground. Using case study methodology, this research examines the perspectives and experiences of industry stakeholders working and living in a dental tourism industry site in northern Mexico to develop a better understanding of the ways in which common discourses of the industry are taken up or resisted by various industry stakeholders and the possible implications of these practices on health equity. Results Interview discussions with a range of industry stakeholders suggest that care provision in this particular location enables international patients to access high quality dental care at more affordable prices than typically available in their home countries. However, interview participants also raised concerns about the quality of care provided to medical tourists and poor access to needed care amongst local populations. These concerns disrupt discourses about the positive health impacts of the industry commonly circulated by industry stakeholders positioned to profit from these unjust industry practices. Conclusions We argue in this paper that elite industry stakeholders in our case site took up discourses of medical tourism as enhancing access to care in ways that mask health equity concerns for the industry and justify particular industry activities despite health equity concerns for these practices. This research provides new insight into the ways in which the medical tourism industry raises ethical concern and the structures of power informing unethical practices.